2002
DOI: 10.1095/biolreprod66.3.685
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase Expression and Activity Following Prostaglandin F2α-Induced Luteolysis1

Abstract: Luteal tissue contains matrix metalloproteinases (MMPs) that cleave specific components of the extracellular matrix (ECM) and are inhibited by tissue inhibitors of metalloproteinases (TIMPs). We previously reported a decrease in luteal TIMP-1 within 15 min of prostaglandin F(2 alpha) (PGF(2 alpha))-induced luteolysis. An increase in the MMP:TIMP ratio may promote ECM degradation and apoptosis, as observed in other tissues that undergo involution. The objectives of these experiments were to determine whether 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…Under conditions in which TIMP-1 levels are increased and MMP13 levels are decreased, there is an increased deposition of fibrillar collagens in the liver. The imbalance between MMP-13 and TIMP-1 can be expressed as the MMP-13/TIMP-1 ratio (Vaillant et al, 2001;Ricke et al, 2002). In this study, we observed antifibrotic effects of both IL10 and M6P-IL10 via the regulation of MMP-13 and TIMP-1 mRNA expressions.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Under conditions in which TIMP-1 levels are increased and MMP13 levels are decreased, there is an increased deposition of fibrillar collagens in the liver. The imbalance between MMP-13 and TIMP-1 can be expressed as the MMP-13/TIMP-1 ratio (Vaillant et al, 2001;Ricke et al, 2002). In this study, we observed antifibrotic effects of both IL10 and M6P-IL10 via the regulation of MMP-13 and TIMP-1 mRNA expressions.…”
Section: Discussionsupporting
confidence: 56%
“…In vivo, the ratio between matrix-degrading activity and inhibition of this activity determines the net outcome of the process. When the ratio of MMP-13 and TIMP-1 was determined (Vaillant et al, 2001;Ricke et al, 2002), we assessed that IL10 and M6PIL-10 both significantly enhanced this ratio (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, MMP3 mRNA was detected in ovine CL and was transiently increased within 30 min of functional luteal regression [40]. We found that, in chicken, MMP3 expression gradually increased with follicular maturation and reached its highest level in F1 follicles.…”
Section: Expression and Regulation Of Mmp3 In The Chicken Ovarymentioning
confidence: 66%
“…A rapid decrease in the MMP3 ZHU ET AL. mRNA was observed in chicken POF follicles, which is in contrast with MMP3 induction during ovine luteolysis [40]. The temporal MMP3 expression pattern indicates that it is probably involved in chicken ovulation but not POF regression.…”
Section: Expression and Regulation Of Mmp3 In The Chicken Ovarymentioning
confidence: 76%
“…Recent reports describe intriguing relationships between metalloproteinases and lipids that are mediated by transcription factors (such as PPARs), lipid carrier proteins (such as apolipoproteins), and lipoparticle receptors (such as LRP-1). GPCRs are among the receptors for lipids and lipids are among the transactivators of metalloproteinases and signaling of the EGFR pathway [149,156,157]. In addition, the GTPases Rho, Rac and Ras, which are associated with the transduction of growth signals from GPCRs, require isoprenylation for their activity [158].…”
Section: Emerging Links Between Lipids and Metalloproteinasesmentioning
confidence: 99%